Integrated HIV self-testing (HIVST) service delivery in Queensland for policy and service development: study protocol. Issue 2 (1st February 2019) - Bell, Sara Fiona Elisabeth; Dean, Judith Ann; Lemoire, Jime; Debattista, Joseph; Driver, Glen; Gilks, Charles F.; Redmond, Andrew; Williams, Owain David
ABSTRACT: This study aims to pilot and evaluate an integrated model for HIV self-testing (HIVST) service delivery in a peer-led Queensland community setting to increase access to HIVST, particularly for men who have sex with men (MSM) living in regional, remote and rural areas. It seeks to provide evidence that would overcome some of the key objections previously raised to HIVST. Recruitment strategies have been designed to engage hard to reach MSM populations in testing. Awareness of the trial will be generated through advertising on social media platforms, including dating applications, word of mouth and HIV related websites. Participants will access an HIVST online ordering system hosted by a HIV community organisation. This system: (1) enables on-line informed consent; 2) gives clients the choice to accept verbal pre-test information from a trained peer test facilitator or not; and (3) allows for ordering of the HIVST kit after completion of an online survey (with demographic information and testing history etc.). Clients receive the kits via the post; and at 2 weeks receive a follow-up phone-call and SMS link to a post-test survey. If the test is non-reactive, clients can opt for test reminders. If reactive, referral to clinical services, peer navigation and support systems are provided. This study addresses important gaps in understanding of acceptable and feasible methods to integrate HIVST into an existing peer-led testing service and into the broader suite of HIV testing options and services. The findings will inform the actions needed to enhance access to HIVST for MSM wishing to use this technology in Australia and elsewhere, especially those who have never tested and infrequent testers.